Analisa Proses Impor Barang Mewah di Daerah Pabean Oleh Penyedia Jasa Barang dan Logistik (Studi Kasus Pada PT. XN Semarang, Indonesia) - Vivid Dekanawati; Sundarti Sundarti; Juan Fajar Kurrniawan Saputra (Majalah Ilmiah Bahari Jogja, 2020)
This study examines the process of importing luxury goods when entering customs areas by a service provider of goods and logistics in Semarang. Luxury goods that are the object of research here are fantastic cost of bicycles. The high use of luxury bicyles in Indonesia also beneficial for industry players, one of which is an importer, even though it makes worry from local bicyces manufactures. Currently, industry players are competing to improve their services or bicycle production the increasingly large market demands. Even the luxury bicycle import activity was not stopped by this Covid-19 pandemic. The import process which is theoretically provided by various sources experiences many differences in the filed starting from import procedures, man import documents, additional import documents, tracking and container status. Even the clarity of the original documents and copy documents that were taken care by various importing agencies had not been clearly stated in the expert theories. In the end not all theoretical basis can be applied/ held on import work in the field. Many factors influence including the process of import activities, the transportation system that influences documensts, the status of shipper and consignee affect the status of the container even the determination of the path determined by the Custom.